A contemporary view of the mechanisms of formation of new contaminants in vegetable oils – esters of monochloropropanediols and high molecular weight carboxylic acids - E. A. Butina; I. A. Dubrovskaya; E. O. Gerasimenko; S. A. Kalmanovich (Новые технологии)
Monochloropropanediols (MCPD) and their esters with high molecular weight carboxylic (fatty) acids are new types of technological contaminants present in refined deodorized oils and other foods.The development of measures to minimize the content of MCPD esters in vegetable oils, which are an important component of various food systems, is a priority direction of modern foreign and domestic research in the field of ensuring food safety. The effectiveness of such measures should be based on ideas about the mechanisms of formation of MCPD esters and the identification of their predecessors (precursors) present in the lipid complex of oil seeds, as well as those formed during their processing.Systematized statistically reliable scientific knowledge about the mechanisms of formation of MCPD esters and their derivatives is still missing. Presumably, the formation of MCPDs and their esters with fatty acids should correlate with the presence of chlorine compounds in oilseed raw materials and in the oil itself; chlorine-containing pesticides and biologically active substances (fertilizers) used in agricultural production are one of the sources.Thus, the goal of the research is a systematic and comprehensive synthesis of ideas about precursors and mechanisms of formation of MCPD esters.As a result of analysis and synthesis of literature sources, it has been established that the main precursors of MCPD esters are DAG, TAG and various chlorine-containing compounds. The main factors influencing the rate of formation and amount of accumulation of MCPD esters are high temperatures (more than 120°C), duration of heat treatment, the presence of free fatty acids, antioxidants and moisture. Different chlorine compounds appear to have different activities in the reactions leading to the formation of MCPD esters. The presence of antioxidants in lipid systems can inhibit the formation of 3-MCPD ester, and the effectiveness of the process is determined by the type of antioxidant. According to the degree of increase in inhibitory ability, the most applicable antioxidants in lipid systems can be ranked as follows: α-tocopherol, BOA, BOT, AP, PG and TBHQ. The role of the composition of fatty acids in the formation of MCPD esters still remains unclear; however, there is indirect evidence indicating the influence of the composition of fatty acids on the level of accumulation of MCPD esters, which determines the feasibility of an in-depth study of this issue.